Il pensiero poetante di Simone Weil - Fulco, Rita (Bollettino Filosofico, 2017)
My reflections start from the principle that philosophy and poetry, far from being opposed, find in Weil’s essentially poetic writing a point of conjunction and of tension that free their potentiality exponentially. At the root of Weil’s poetry, the thinking that inspires it condenses a theoretical reflection that interacts where aesthetics, ethics, politics and religious tension cross, so that the Beautiful cannot be dissociated from the Good and the Just, in the same way as the Natural only can open up to the Supernatural.